Lack of Public Relations Role in the Use of Instagram as a Publication Tool to Improve Community Services at the Salimpaung District Health Center (Case Study on Instagram Account puskesmas salimpaung) - Fajar G, Djorgi; Bernd , Engly; Erland, Jhony; Alurs, Yert (Journal International Dakwah and Communication, 2022)
Media is a tool for conveying messages to the general public, then the field of public relations does not escape the name of the media because public relations needs the media to publish information about companies or organizations. In the process of performance, the Salimpaung Health Center certainly needs to convey information to its audience about whether it is necessary to receive programs, services, and so on. This does not include media information for such programs and information. This study aims to analyze the role of public relations on Instagram social media as a publication to improve community services at the Salimpaung District Health Center. The research method in this study is qualitative, with descriptive research using case studies. Data collection techniques in this study by conducting interviews with Deep, seeing the results of posts from the Salimpaung Health Center related to the activities and role of the health center as community services. The role of public relations is the role of expert advisor, the role of communication facilitator, the role of facilitator of problem-solving processes, and the role of communication technician. Public Relations are categorized as less active in using Instagram as a means of publication at the Salimpaung Health Center, through the results of research related to the salimpaung health center public relations.